Effectiveness of different medical interventions implemented when a change in hearing status is detected during ototoxicity monitoring - Gangerdine, Kayleen (Division of Communication Sciences and Disorders, 2022)
Background: Fourteen thousand (14, 000) people fell ill with Multi-Drug Resistant (MDR) or Rifampicin-Resistant (RR) Tuberculosis (TB) in South Africa (SA) in 2019. Aminoglycosides, which are commonly used anti-tuberculosis drugs in the treatment for RR/MDR-TB patients, are associated with ototoxicity (cochlear or vestibular). Aminoglycoside-induced cochleotoxicity is characterised by permanent, bilateral, highfrequency (HF) sensorineural hearing loss (SNHL). The impact of hearing loss (HL) due to aminoglycoside-induced cochleotoxicity can influence a patient's communication, psychological, physical functioning and overall well-being negatively and lead to a reduced quality of life (QoL). To reduce the risk of aminoglycoside-induced cochleotoxicity, patients' hearing thresholds are monitored (i.e., cochleotoxicity monitoring) when they are being treated with cochleotoxic aminoglycosides. Cochleotoxicity monitoring is performed to detect a significant threshold shift (STS) early and prevent further deterioration of hearing thresholds and avoid hearing loss which may end up affecting frequencies that are important for speech perception. When a STS or hearing loss is detected during cochleotoxicity monitoring, there are various intervention strategies that can be implemented by the treating medical personnel to avoid further deterioration of patient's hearing thresholds. These strategies may include discontinuing the aminoglycoside, changing the aminoglycoside to a less cochleotoxic alternative in the regimen or changing the frequency of administration of the aminoglycoside. This study, therefore, aimed to determine the effectiveness of different strategies used when a STS in hearing occurred during cochleotoxicity monitoring to prevent further deterioration in hearing thresholds. Methodology: A descriptive prospective repeated-measures design was used in this study. Patients who underwent RR/MDR-TB treatment with Kanamycin, a cochleotoxic aminoglycoside, at Brooklyn Chest Tuberculosis Hospital (BCH) between June to December 2016 were recruited to participate in the study. Only patients (n= 69) with normal hearing thresholds (i.e., pure tone average (PTA) at 500 Hz, 1 kHz and 2 kHz ≤ 25 dB HL) at baseline and age 18 – 55 years were included. Patients who were receiving two aminoglycosides, were retreatment patients or had active middle ear (ME) pathology were excluded from this study. Participants were sampled via a purposive sampling strategy. All audiological testing was performed in a sound-treated booth and participants underwent the following types of assessment; baseline, periodic monitoring, and diagnostic assessment (when indicated). The following tests were performed at baseline: case history, otoscopy (OT), tympanometry (TYMP), conventional pure tone audiometry (cPTA) including air conduction (AC) and bone conduction (BC), and ultra-high frequency audiometry (UHFA). Follow-up monitoring assessment occurred monthly if there was no significant change in hearing thresholds, and biweekly if an STS was detected. The ASHA criteria were used to determine STS. The degree of hearing loss was described as mild, moderate, moderately-severe, severe or profound and the type of hearing loss was either conductive, sensorineural, or mixed. Both descriptive and inferential (Chi-squared, Mann-Whitney U and Kruskal-Wallis) statistical tests were used for data analysis. Results: A total of sixty-nine (69) patients who were undergoing treatment for RR/MDR-TB were recruited to participate in this study. Five participants dropped out of the study due to various reasons, therefore, leaving 64 participants in the study. There was 38 males and 26 females. The median age was 31 [range; 18 - 55] years old. An aminoglycoside-induced cochleotoxicity incidence of 90.6% (58/64) was found in this study. There were no statistically significant associations between the occurrence of STS and age (p = 0.487), sex (p = 0.329) and HIV status (p = 0.764). Three types of intervention strategies were used when a participant experienced an STS: (i) discontinue Kanamycin (Strategy A), (ii) modify the frequency of Kanamycin administration (Strategy B), (iii) and leave the regimen unchanged, i.e., no intervention (Strategy C). A smaller proportion of participants, 12 out of 33, experienced further deterioration of hearing thresholds after intervention strategy A (discontinue Kanamycin) was used, when compared to participants who underwent intervention strategies B and C, but the difference was not statistically significant (p = 0.056). Conclusion: This study found a high incidence of cochleotoxicity among patients receiving Kanamycin treatment for RR/MDR-TB. The results showed that discontinuing Kanamycin led to fewer participants developing further deterioration of hearing thresholds, although not statistically significant. There were no statistically significant associations between the occurrence of STS and age, sex, and HIV status. This study had some limitations; only cochlear hearing loss was investigated, participants were not followed up beyond six months, and genetic testing was not performed. Nonetheless, this study revealed that fewer participants had further significant threshold shifts after discontinuing Kanamycin, and for those patients who still receive regimens containing aminoglycosides, these findings are relevant.